(3MOjbI GdQjGVjGJ dQjGV GdCWaGds (3GdeSJhi GdChds ((3GdbGgQIs (3SajQs, 2003)
(3QMdI eeJYI jJLhd GdWad NdGdgG Hjf YGde GdCQbGe hGdeaGgje hjSJeJY ajgG HGdYOjO ef GdCfTWI GdeNJdaI ef bUU GdCQbGe hGdHGRd hGdJdhjf hGdCdYGH , gh HQfGeL eJejR hKQj jMbb GdJaGYd Hjf GdWad hGdQjGVjGJ HCSdhH Sgd hLejd hjcJSH GdWad ef NdGd GdHQfGeL GdYOjO ef GdegGQGJ GdJj Jfej PcGAg hbOQGJg Ydj GdJacjQ hGdEHJcGQ hJfejI GdhYj hGdCSJOdGd dOi GdWad hJfejI GdbOQI Ydj GdJejjR hGdJPcQ hGdJNjd hJfejI bhI GdedGMXIs
(3eQab cJGH eY GdbQU GdVhFjs
(3fXGe JTZjd hjfOhR (Bxp (3Ch Cbd , YQHj Ch EfLdjRj , (B32 (3ejLGHGjJ ef GdPGcQI (Bram (3, CdhGf (B24 bits
8 13
Keywords: (3GdQjGVjGJs -- (3JYdes -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjGs -- (3CWaGds -- (3ehGO SeYjI hHUQjIs